From analysis to visualization : a celebration of the life and legacy of Jonathan M. Borwein, Callaghan, Australia, September 2017 /: a celebration of the life and legacy of Jonathan M. Borwein, Callaghan, Australia, September 2017. (©2020) - Unknown
No abstract available